Pengembangan Ekosistem Pelayanan Publik Digital Terpadu di Kelurahan Sukagalih Kabupaten Garut - Murti, Yusza Reditya; Irawan, Herry; Ramadhani, Dian (Transpublika Publisher, 2025)
Digital transformation in public services has emerged as an urgent necessity to enhance operational efficiency and effectiveness across various levels of government. Sukagalih Village, located in Tarogong Kidul District, Garut Regency, with a population of 17,145 residents and 12,000 households, faces complex challenges in public service delivery. The primary issues encompass manual administrative systems that cause operational inefficiencies, challenges in tracking demographic data for social assistance and community empowerment programs, and fragmented regional monographic data that hinders data-driven decision-making. Additional challenges including risks of illegal levies and lack of transparency in public services further reinforce the urgency for digital solution implementation. This research aims to develop an integrated digital public service ecosystem that incorporates administrative service management information systems and geospatial-based analytics dashboards in Sukagalih Village. The system development approach follows the System Development Life Cycle (SDLC) framework with the Scrum methodology, involving village officials participatively throughout each development stage. The system is designed reduce physical office visits, featuring document upload capabilities through digital platforms and analytics dashboards for empowerment program monitoring. The implementation of this digital ecosystem is expected to reduce administrative document processing time, improve the accuracy of regional monographic data with precise geospatial coordinates, minimize illegal levy practices, and enhance transparency and accountability in public services. The research outcomes are projected to serve as a smart village model that can be adopted by other villages or sub-districts in realizing transparent, accountable, and data-driven governance.